Further new names and combinations in Scrophulariaceae–Manuleae - Hilliard, O. M. (Edinburgh Journal of Botany, 2010)
Lyperia canariensis and Urbania lyperiiflora are transferred to Camptoloma Benth; Manulea antirrhinoides is transferred to Lyperia Benth., and one species of Lyperia is newly described; fifteen species and one subspecies of Sutera are newly described, and one new combination is made.